PENDIDIKAN KARAKTER RELIGIUS PADA SISWA DI SEKOLAH DASAR ATTARBIYAH AL-ISLAMIYAH - M. Muslih (Universitas Muhammadiyah Surabaya, 2022)
Religious character education is an attempt to realize the religious values contained in the Qur'an and Al-Hadith into a person. The purpose of this study was to determine the process of religious character education in students at the Attarbiyah Al-Islamiyah elementary school and to determine the supporting and inhibiting factors. This research uses field research with a qualitative approach. The subjects in this study were 3 teachers, namely PAI teachers, homeroom teachers and foundation teachers. While the object of this research is the process of religious character education. Data collection techniques using interviews and documentation. as for data processing techniques are data collection, data reduction, data presentation and data verification. data analysis using descriptive analysis. The results of this study indicate that the process of religious character education for students in elementary schools at Attarbiyah Al-Islamiyah the teachers carry out several activities, namely learning activities such as respecting parents and teachers, routine activities such as reading prayer prayers, reading the Koran before studying, Friday piety. as well as congregational midday prayers, spontaneous activities such as behaving in a disciplined manner, exemplary and there is always motivation for students to behave religiously. The supporting factors are the personality of the teacher, the support from parents, the joint commitment of the school community, and adequate facilities. The inhibiting factors are electronic media and the lack of awareness of students.Â Keywords: Education; Character; Religious